Dynamique d’acteurs (agriculteurs et institutions) et innovation agro-écologique pour la gestion des risques environnementaux en Guadeloupe - Marie Houdart; Muriel Bonin; Ludovic Temple (VertigO)
The aim of our research is to urge a reflexion on the agro-ecological innovations to manage the environmental risks. We analyse the organization that the stakeholders (farmers and institutions) set up facing the crises and disturbances which touch the agriculture of French West Indies. To do this, we enquired a group of farmers of banana production in Guadeloupe, and also the agricultural and environmental institutions of this island. This made it possible to identify three principal conclusions on the nature of the innovations, their scale of application and the driving forces which underlie them: from a technical point of view, new practices are implemented independently of the exchanges between farmers; from a strategic point of view, changes of production are made, depending on exchanges dynamic; on the level of the institutions, new places of dialogue are created. In conclusion, there is a shift in the dynamics of dialogue according to the levels of organization (farmers versus institutions) and the bond between these two levels of organization seems to be very thin.